The MMPI-2/MMPI-2-RF : an interpretive manual - Greene, Roger L., ....- (Boston (Mass.) : Pearson education, 2011)
Evolution of the MMPI -- Administrative issues -- Assessing validity -- Clinical scales -- Codetypes -- Content scales -- Supplementary scales -- Restructured form (RF) -- Conceptual framework -- MMPI-2 and MMPI-2-RF interpretation -- Demographic variables -- Adolescents and aged.
Rev. ed. of: The MMPI-2 : an interpretive manual. 2nd ed. 2000.
Includes bibliographical references (p. 581-612) and indexes.
Keywords: Minnesota Multiphasic Personality Inventory; Psychologische tests